2022
DOI: 10.1186/s44149-022-00053-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene expression in human brain microvascular endothelial cells in response to the infection of influenza H1N1 virus

Abstract: Influenza viruses not only cause respiratory illness, but also have been reported to elicit neurological manifestations following acute viral infection. The central nervous system (CNS) has a specific defense mechanism against pathogens structured by cerebral microvasculature lined with brain endothelial cells to form the blood–brain barrier (BBB). To investigate the response of human brain microvascular endothelial cells (hBMECs) to the Influenza A virus (IAV), we inoculated the cells with the A/WSN/33 (H1N1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The disease has rapid onset and progression, with a high mortality rate in severe patients and varying degrees of neurological sequelae in survivors ( 22 ). However, the pathogenesis of ANE is still unclear, and studies have shown an association with high levels of cytokines in plasma and cerebrospinal fluid, particularly interleukin (IL)6, tumor necrosis factor (TNF)alpha, leading to a storm of cellular inflammatory factors that induce innate and inflammatory immune responses ( 23 , 24 ). In Japan, ANE had the highest incidence in the 0–4 age group from 2004 to 2009, but a new change occurred during influenza A(H1N1) from 2009 to 2010, with the highest incidence in the 5–9 years age group.…”
Section: Discussionmentioning
confidence: 99%
“…The disease has rapid onset and progression, with a high mortality rate in severe patients and varying degrees of neurological sequelae in survivors ( 22 ). However, the pathogenesis of ANE is still unclear, and studies have shown an association with high levels of cytokines in plasma and cerebrospinal fluid, particularly interleukin (IL)6, tumor necrosis factor (TNF)alpha, leading to a storm of cellular inflammatory factors that induce innate and inflammatory immune responses ( 23 , 24 ). In Japan, ANE had the highest incidence in the 0–4 age group from 2004 to 2009, but a new change occurred during influenza A(H1N1) from 2009 to 2010, with the highest incidence in the 5–9 years age group.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, to extend the period of viral replication, JEV may interfere with the apoptotic pathway of transfected human brain microvascular endothelial cells (hBMECs) [ 8 ]. Aside from their well-characterized barrier function, BMECs can be immune activated to mount effective IFN induction and IFN-stimulated gene (ISG) expression as a response to viral infections, including human immunodeficiency virus (HIV), Zika virus (ZIKV), and influenza virus [ 11 13 ]. In restricting WNV transit, IFN-λ signaling promotes BMEC barrier tightening [ 14 ].…”
Section: Introductionmentioning
confidence: 99%